Incidence and clinical relevance of non-small cell lung cancer lymph node micro-metastasis detected by staging endobronchial ultrasound-guided transbronchial needle aspiration - Belanger, Adam R.; Hollyfield, Johnathan; Yacovone, Gabriella; Ceppe, Agathe S.; Akulian, Jason A.; Burks, A. Cole; Rivera, M. Patricia; Dodd, Leslie G.; Long, Jason M.; Haithcock, Benjamin E.; Pecot, Chad V. (Journal of Thoracic Disease; Vol 11, No 8 (August 31, 2019): Journal of Thoracic Disease, 2019)
Background: Approximately twenty percent of lymph node (LN) negative non-small cell lung cancer (NSCLC) patients who undergo curative intent surgery have pan-cytokeratin immunohistochemistry (IHC)-detectable occult micro-metastases (MMs) in resected LNs. The presence of the MMs in NSCLC is associated worsened outcomes. As a substantial proportion of NSCLC LN staging is conducted using endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA), we sought to determine the frequency of detection of occult MMs in EBUS-TBNA specimens and to evaluate the impact of MMs on progression-free and overall survival. Methods: We performed retrospective IHC staining for pan-cytokeratin of EBUS-TBNA specimens previously deemed negative by a cytopathologist based on conventional hematoxylin and eosin staining. The results were correlated with clinical variables, including survival outcomes. Results: Of 887 patients screened, 44 patients were identified meeting inclusion criteria with sufficient additional tissue for testing. With respect to the time of the EBUS-TBNA procedure, 52% of patients were clinical stage I, 34% clinical stage II, and clinical 14% stage IIIa NSCLC. Three patients (6.8%) were found to have cytokeratin positive MMs. All 3 MMs detected were at N2 LN stations. The presence of MMs was associated with significantly decreased progression-free (median 210 vs. 1,293 days, P=0.0093) and overall survival (median 239 vs. 1,120 days, P=0.0357). Conclusions: Occult LN MMs can be detected in EBUS-TBNA specimens obtained during staging examinations and are associated with poor clinical outcomes. If prospectively confirmed, these results have significant implications for EBUS-TBNA specimen analyses and possibly for the NSCLC staging paradigm.